2004
DOI: 10.1089/mdr.2004.10.269
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Model and Molecular Mechanism ofMycobacterium tuberculosisCatalase-Peroxidase (KatG) and Isoniazid-Resistant KatG Mutants

Abstract: Mycobacterium tuberculosis KatG enzyme functions both as catalase for removing hydrogen peroxide (H 2 O 2 ) and as peroxidase for oxidating isoniazid (INH) to active form of anti-tuberculosis drug. Although mutations in M. tuberculosis KatG confer INH resistance in tuberculous patients, structural bases for INH-resistant mutations in the KatG gene remains poorly understood. Here, three M. tuberculosis KatG mutants bearing Arg418→ Gln, Ser315 → Thr, or Trp321 → Gly replacement were assessed for changes in catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Similar to changes to the Trp, changes to the Tyr or Met, or even Arg 426 associated with Tyr 238, inhibited the catalase reaction, with little or no effect on the peroxidase reaction (Jakopitsch et al, , 2004Yu et al, 2003;Singh et al, 2004). A mechanism attempting to explain why these residues are essential for the catalase reaction has been postulated (Mo et al, 2004), but is incompatible with recent data. a BpKatG_7.5, crystal at pH 7.5; BpKatG_8.0, crystal at pH 8.0; OF_5.6, oxyferryl species at pH 5.6; OF_7.5, oxyferryl species (generated at pH 5.6 and shifted to pH 7.5) from the composite data set described in Methods.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar to changes to the Trp, changes to the Tyr or Met, or even Arg 426 associated with Tyr 238, inhibited the catalase reaction, with little or no effect on the peroxidase reaction (Jakopitsch et al, , 2004Yu et al, 2003;Singh et al, 2004). A mechanism attempting to explain why these residues are essential for the catalase reaction has been postulated (Mo et al, 2004), but is incompatible with recent data. a BpKatG_7.5, crystal at pH 7.5; BpKatG_8.0, crystal at pH 8.0; OF_5.6, oxyferryl species at pH 5.6; OF_7.5, oxyferryl species (generated at pH 5.6 and shifted to pH 7.5) from the composite data set described in Methods.…”
Section: Introductionmentioning
confidence: 96%
“…Similar to changes to the Trp, changes to the Tyr or Met, or even Arg 426 associated with Tyr 238, inhibited the catalase reaction, with little or no effect on the peroxidase reaction (Jakopitsch et al , 2003, 2004; Yu et al , 2003; Singh et al , 2004). A mechanism attempting to explain why these residues are essential for the catalase reaction has been postulated (Mo et al , 2004), but is incompatible with recent data.…”
Section: Introductionmentioning
confidence: 97%
“…Even though katG (S315T) has catalase and peroxidase activities, it is less efficient than KatGWT in the isoniazid metabolism [ 14 ]. Modification of the INH binding site due to the S315T mutation is a significant factor in the decline of the mutant activity to activate isoniazid [ 15 ] [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the KatG active sites globally resembles that of mono-functional peroxidases, in the detail there are significant differences on the heme environment. Recent investigations based on structural aspects [2,3,12,13] as well as kinetic characterization of selected variants of the heme environment [14][15][16][17]19] have given the basis to better understand the contribution of such differences in the remarkable reactivity of KatGs, as compared to mono-functional peroxidases. For example, it has been shown that the very unusual adduct resulting from the crosslink of three residues of the heme distal side, namely Trp122, Tyr249 and Met275 (Synechocystis numbering) is crucial for the catalatic activity of KatGs.…”
Section: Introductionmentioning
confidence: 99%